Keefektifan model guided inquiry terhadap keterampilan berpikir kritis peserta didik kelas v pembelajaran ipas materi organ pernapasan di sekolah dasar - Al Fatikhah, Aulia Fadia; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2025)
This study aims to examine the effectiveness of the guided inquiry learning model in improving the critical thinking skills to fifth-grade students in the IPAS (Natural and Social Sciences) subject at SDN Cengklik, as well as to identify the challenges fade. The background of the study is the low critical thinking skills of students due to the lack of variety in the teaching models used. The purpose of this study are : a) Knowing the mechanism of the Inquiry Mwthod can be used to improve critical thinking skills, b) Knowing the rolse of thinking, c) Knowing the characteristics of the critical thinking. The study employs a quasi-experimental method with a pretest-posttest nonequivalent control group design, and the sample is selcted through purposive sampling. Data analysis is conducted using the independent sample t-test with spss 25. The results show that the guided inquiry model signuficantly that this model students’s crotical thinking skills compared to conventional teaching methods, indicating that this model is effective use in ipas instruction.